Evaluation of extracts from Phyllostachys makinoi for their antibacterial and accelerated wound healing potential - Te-Hua Liu; Ju-Yun Wu; Meng-Chun Cheng; Bang-Yuan Chen; Tsung-Yu Tsai (AMB Express)
Abstract Phyllostachys makinoi, an endemic bamboo species in Taiwan, is underutilized, despite its rich forest resources. Known for its antioxidant, anti-inflammatory, and antibacterial properties, this study explores the antimicrobial, anti-inflammatory, and wound-healing activities of P. makinoi extracts. The antibacterial potential of P. makinoi extracts was first evaluated using the agar diffusion method, along with minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) assays. Subsequently, electron microscopy and a conductivity meter were employed to assess whether P. makinoi extracts exert antibacterial effects by disrupting bacterial cell structures. Finally, the anti-inflammatory and cell proliferation-promoting effects of P. makinoi extracts were assessed in RAW264.7 and CCD-1112Sk cell models. The MIC and MBC of the P. makinoi water extracts against two multidrug-resistant Staphylococcus aureus strains were 4 and 16–32 mg/mL, respectively, while those for ethanol extracts were 2 and 32 mg/mL, respectively. In the time-kill assay, both strains were killed after treatment with extracts for 12 and 18 h. Scanning electron microscopy revealed that the bacterial cells treated with the extracts appeared rough, ruptured, and shriveled. The extracts disrupted the cell membranes, causing electrolyte, protein, and nucleic acid leakage, leading to cell death. Additionally, P. makinoi extracts reduced lipopolysaccharide-induced nitric oxide, tumor necrosis factor-α, interleukin (IL)-1β, and IL-6 levels in RAW264.7 cells, and promoted wound healing by enhancing CCD-1112Sk cell proliferation. In conclusion, P. makinoi water and ethanol extracts demonstrated antibacterial and anti-inflammatory effects, showing potential for treating wound infections and accelerating healing, making them promising candidates for wound-healing therapies.